2011
DOI: 10.5251/abjna.2011.2.3.462.470
|View full text |Cite
|
Sign up to set email alerts
|

Litter fall and decomposition trend of jatropha curcas L. leaves mulches under two environmental conditions

Abstract: The study was conducted at the Faculty of the Forest Resources Technology, Sunyani, Ghana, with the objective of finding out the litter fall and the decomposition trend of Jatropha curcas leaf mulches. A 2 mm nylon mesh size fitted to stakes at 1 m above the ground was used to trap the leaf litter and their oven dry weights taken. Decomposition of Jatropha curcas leaf litter was assessed by placing 80 g fresh leaf in a 0.30 m x 0.30 m nylon litter decomposition bags of 2 mm mesh size at two (2) different envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…According to the same study by Abugre et al [19], after 120 days of decomposition, between 2.45 and 34.6% carbon is still left from Jatropha curcas litterfall. The large difference in the decomposition rate is due to the difference in sunlight exposure on the litterfall [20].…”
Section: Discussionmentioning
confidence: 91%
“…According to the same study by Abugre et al [19], after 120 days of decomposition, between 2.45 and 34.6% carbon is still left from Jatropha curcas litterfall. The large difference in the decomposition rate is due to the difference in sunlight exposure on the litterfall [20].…”
Section: Discussionmentioning
confidence: 91%
“…Differences in leaf biomass that is size and number [29,40], tree crown architecture and phenology [38,41] amongst tree species are some of the factors found to influence amounts of leaf fall. The higher amounts of leaf fall registered in the dry season as compared to the wet season could be attributed to harsh climatic conditions of high temperatures, wind speed, low precipitation, low soil moisture and atmospheric humidity that increase natural leaf senescence [27,28,41,42]. Leaf litter-fall was noted to have decreased with increasing pruning intensity for all the selected tree species (Table 2).…”
Section: Leaf Fall and Pruned Leaf Biomassmentioning
confidence: 99%
“…Leaf litter fall was collected from the three pruning regimes (0%, 25% and 50%) using the litter trap technique [14,27,28]. To collect the falling leaves, a 1m × 1 m trap was constructed from a strong nylon mesh suspended on a frame of four wooden pole stands erected, 0.90m above the ground (Figure 1).…”
Section: Leaf Litter Fall Collection and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing for the incorporation of the dry leaf mulch into the soil was based on work by Abugre et al (2011) who reported that in Ghana 50 % decomposition of jatropha leaf litter was obtained after 25 days in an open canopy and 32 days in a closed canopy. In total 97 % to 99 % of leaf litter had decomposed after 120 days, which was consistent with the maize nutrient requirements.…”
Section: Fertility Competition and Interaction Effects Of Jatropha mentioning
confidence: 99%